Self-reported and actual adherence to the Tokyo guidelines in the European snapshot audit of complicated calculous biliary disease. Issue 4 (17th May 2020) - Bass, G A; Gillis, A E; Cao, Y; Mohseni, S; Shamiyeh, A; Rosetti, L; Klimbacher, G; Klugsberger, B; Healy, P; Moriarty, C; Power, C; Knightly, N; et al.
Abstract: Background: Complicated acute biliary calculous disease poses clinical challenges. The European Society of Trauma and Emergency Surgery (ESTES) snapshot audit of complicated biliary calculous disease aims to make novel comparisons between self-reported institutional adherence to the Tokyo guidelines (TG18) and 'real-world' contemporary practice across Europe. Methods: A preplanned analysis of a prospective observational multicentre audit that captured patients undergoing emergency admission for complicated biliary calculous disease (complicated cholecystitis, biliary pancreatitis, or choledocholithiasis with or without cholangitis) between 1 and 31 October 2018 was performed. An anonymized survey was administered to participating sites. Results: Following an open call for participation, 25 centres from nine countries enrolled 338 patients. All centres completed the anonymized survey. Fifteen centres (60 per cent) self-reported that a minority of patients were treated surgically on index admission, favouring interval cholecystectomy. This was replicated in the snapshot audit, in which 152 of 338 patients (45·0 per cent) underwent index admission cholecystectomy, 17 (5·0 per cent) had interval cholecystectomy, and the remaining 169 (50·0 per cent) had not undergone surgery by the end of the 60-day follow-up. Centres that employed a dedicated acute care surgery model of care were more likely to perform index admission cholecystectomy compared with a traditional general surgery 'on call' service (57 versus 38 per cent respectively; odds ratio 2·14 (95 per cent c.i. 1·37 to 3·35), P < 0·001). Six centres (24 per cent) self-reported routinely performing blood cultures in acute cholecystitis; patient-level audit data revealed that blood cultures were done in 47 of 154 patients (30·5 per cent). No centre self-reported omitting antibiotics in the management of acute cholecystitis, and 144 of 154 (93·5 per cent) of patients in the snapshot audit received antibiotics during their index admission. Conclusion: Awareness of TG18 recommendations was high, but self-reported adherence and objective snapshot audit data showed low compliance with TG18 in patients with complicated acute biliary calculous disease. Graphical Abstract: The Tokyo Guidelines 2018 (TG18) describe expert consensus for best practice in the management of complex acute biliary calculous disease. Self-reported adherence (and limitations to this) were compared with 'real-world' patient-level data from a prospective observational study, the ESTES snapshot audit. Recognition of TG18 was high, but adherence to guidance on both index admission cholecystectomy and microbiological culture-guided antibiotic therapy was poor. Low self-reported and actual adherence to guidelines